Patophysiology of nonalcoholic fatty liver disease - Krzewicka-Romaniuk, Ewa; Siedlecka, Dagna; Makuch, Marcelina; Pradiuch, Anna; Wójcicka, Grażyna (Journal of Education, Health and Sport, 2019)
Clinically, NAFLD is the most common cause of asymptomatic increases in transaminases. NAFLD is also currently the most common liver disorder in developed countries, affecting 24% of the world's population. The prevalence of NAFLD in European societies is estimated in the range of 17-46% and shows an upward trend with the increasing incidence of obesity and type II diabetes. NAFLD occurs in about 7% of people without excess weight, however, they are usually people with impaired insulin sensitivity, leading a sedentary lifestyle, having an increased cardiovascular risk, with higher levels of hepatic lipids as a result of reduced fat accumulation and reduced mitochondrial activity in adipose tissue and increased de novo hepatic lipogenesis.